GOVERNMENT EFFORTS IN POVERTY ALLEVIATION THROUGH THE SUSTAINABLE DEVELOPMENT GOALS (SDGs) PROGRAM (Sustainability (STPP) Theory, Practice and Policy, 2023)
Poverty is a big concern for developing countries, including Indonesia. Poverty must be recognized and addressed as a global problem, therefore and must also be addressed from a global perspective. Handled as a global problem, therefore this issue must also be addressed from a global perspective. Therefore, every poverty alleviation program must be understood holistically and combined with a number of other operational initiatives. The main priority for SDGs is to eradicate poverty. This shows that the whole world has decided to eradicate it and is determined to eradicate poverty in all its forms, including in Indonesia. Poverty in all its forms, including in Indonesia. eradicating this disease will be closely linked to other global goals, such as eliminating hunger, good health and happiness, higher education, gender equality, clean water and sanitation, clean and cheap energy. Partnerships are needed to achieve this goal. The purpose of this article is to confirm whether the government has maximized the SDGs program for poverty. Library research strategies are used in conjunction with descriptive qualitative research methodology. Learning study library techniques are a collection of studies on how to obtain data from libraries, read and take notes, and process research materials. The goal of a literature review is to relate current research to previously published literature, to fill gaps in previous research, and to inform readers of the results of other research that is relevant to the research being conducted at that time. The result of this article is a detailed explanation regarding the problem of the Government's efforts to eradicate poverty through the Sustainable Development Goals (SDGs) program.